Peningkatan Pemahaman Nilai-Nilai Anti Korupsi Guru Dan Siswa Di Lingkungan Sekolah Sman 1 Kota Serang Provinsi Banten - Furqon, Eki; Rayhan, Ahmad; Vitrana, Mokhamad Gisa; Muslih, Muhamad (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
Instilling anti-corruption values is something that must be done from children to adults, and is done anywhere, even in schools or learning places, especially for high school students in Serang City. These Anti-Corruption Values must be taught and practiced in schools so that they can be brought and practiced to society by students, so that opportunities for committing Corruption in everyday life can be minimized. Teachers as educators also have an important role in directing students not to commit corruption, no matter how small, in real life. The instillation of Anti-Corruption Values is in accordance with the 9 Integrity Values issued by the Corruption Eradication Commission which are believed to be able to prevent criminal acts of corruption, namely including the values of "honesty, caring, independence, discipline, responsibility, hard work, simplicity, courage and fairness." â€. Methods for Increasing Understanding of Anti-Corruption Values are carried out through Socialization and Dialogue with Students of SMAN 1 Serang City and Training of Trainers for Teachers of SMAN 1 Serang City, Program for Increasing Anti-Corruption Values for Teachers and Students in the SMAN 1 City School Environment Serang is an application of the JAWARA Values (Honest, Fair, Dignified, Trustworthy, Religious and Accountable) at Sultan Ageng Tirtayasa University in eradicating criminal acts of corruption both on campus and in the communities of Serang and Banten cities. Apart from that, this activity to increase Anti-Corruption Values is also an embodiment of Untirta's vision of "Character", so this is Untirta's commitment to creating not only students but also people with character, so that this activity to increase Anti-Corruption Values is one of UNTIRTA's commitments. to move together with the community in eradicating corruption and becoming a spring that refreshes the thirst of the surrounding community. One of the efforts made by universities in the Anti-Corruption Values Improvement program is by providing outreach to students of SMAN 1 Serang City as well as Training of Trainers for Teachers of SMAN 1 Serang City. It is hoped that this socialization activity can instill an anti-corruption culture for students at SMAN 1 Serang City and become a guide for teachers at SMAN 1 Serang City in directing students to reject all forms of corruption from various small things in everyday life. So that an Anti-Corruption Culture can be created, especially in Serang City.